Gut Microbiota and Mental Health: A Review of the Impact of Gut Bacteria on Depression and Anxiety Disorders - Pelczarska, Aleksandra; Kaczorowski, Rafal; Forenc, Tomasz; Hunia, Jaromir; Górny, Julia; Janiszewski, Michał; Jurek, Jonasz; Komorowski, Marcin; Kapciak, Alicja (Quality in Sport, 2024)
The gut microbiota plays a crucial role in human health, including mental health. Depression and anxiety disorders are among the most common mental illnesses in the population. This review examines recent PubMed literature to evaluate the microbiota’s impact on these conditions and potential therapeutic strategies. Gut microbiota affects depression and anxiety through neural, endocrine, and immune-inflammatory mechanisms, involving factors such as BDNF, elevated cortisol during dysbiosis, bacterial endotoxins, and cytokines. Conditions like leaky gut syndrome and SIBO are linked to the development of depression, anxiety, and other disorders, such as autism. Probiotics and prebiotics may alleviate depression by enhancing neuroplasticity, though this effect is better established in animal studies. For anxiety disorders, most studies report unfavorable alterations in gut microbiota composition among affected patients, while a few suggest a beneficial effect of probiotics. Probiotics also reduce side effects of antipsychotic drugs. Antibiotic use has been associated with increased risks of these mental conditions. Attempts have been made to use microbiota transfer therapy (MTT) as a complementary treatment, showing improvements particularly in depression and, to a lesser extent, anxiety, especially among patients recovering from COVID-19, those with irritable bowel syndrome (IBS), and individuals with severe depression. In recent years, numerous studies have explored the impact of gut microbiota on mental health, highlighting its significant therapeutic potential as an adjunct in treating anxiety and depression. However, there remains a need for more well-designed, large-scale human studies to confirm these findings conclusively.